AN ACCIDENTAL DEATH BY TRAUMATIC ASPHYXIA ñ A CASE REPORT (Journal of Forensic Medicine & Toxicology, 2011)
On 25/09/04 at about 5:45 pm, a lorry (a heavy motor vehicle – six wheeler) was unloading sugarcane. A bundle containing 50-60 fresh sugarcane fell on a 6 year old boy. The boy was playing in the vicinity of the lorry. The bundle fell on the body of the deceased which was noticed after about thirty minutes. The laborers removed the bundle on his chest and rushed him to hospital. He was declared dead on arrival to J.S.S. Medical College and Hospital, Mysore at about 9 pm. Body was sent to the department of Forensic Medicine J.S.S. Medical College for post-mortem examination. The findings were of intense asphyxia suggestive of death by traumatic asphyxia.
Keywords: Asphyxia; Petechiae; Sugarcane bundle; Blunt trauma